Clinical and echocardiographic course in takotsubo cardiomyopathy: Longterm followup from a multicenter study. (1st February 2017) - MatabuenaGomez-Limon, Javier; IsazaArana, Sebastian; Robledo-Carmona, Juan; AlaniaTorres, Edgar; TorresLlergo, Javier; Valle-Racero, Juan Ignacio; LopezPardo, Francisco; Martinez-Martinez, Angel; Jimenez-Navarro, Manuel; Urbano-Moral, Jose Angel
Abstract: Objectives: To jointly describe clinical characteristics, ECG and echocardiographic findings, and adverse cardiovascular events in patients with tako-tsubo cardiomyopathy (TC) in the long-term. Methods: Longitudinal multicenter study including retrospective analysis of clinical and ECG data, and follow-up evaluation with clinical interview, electrocardiogram and echocardiogram. Results: Data from 66 cases of TC were available for analysis of clinical and adverse cardiovascular events, and 56 of them completed the follow-up visit including electrocardiogram and echocardiogram. Most patients (97%) were asymptomatic or oligosymptomatic (NYHA I [58%] or II [39%], respectively) at follow-up (median time: 3.7 [1.8–6.6] years). The vast majority of individual QRS complex and repolarization abnormalities had disappeared (87% with no ECG abnormalities at follow-up). On echocardiography, left ventricular ejection fraction was ≥ 50% in all patients (mean: 63 ± 6%). Wall motion abnormalities were observed in 4 patients (7%; 3 with apical wall motion abnormalities and 1 with mild global hypokinesia). Long-term outcomes were as follows: 4 deaths (6%), 2 cardiovascular and 2 non-cardiovascular; no atrial fibrillation development; no stroke events; 5 acute recurrence events of TC (8%). Globally, 57 patients (86%) had a clinical course free from adverse cardiovascular events. Conclusions: After a long period following the admission event, patients discharged from TC remain asymptomatic or minimally symptomatic, and feature a low prevalence of both ECG and left ventricular wall motion abnormalities; moreover, the latter lead to a very mild impairment of ejection fraction. Among cardiovascular adverse events, recurrence of the TC event appears to play the most significant role.